2002
DOI: 10.1007/s00401-002-0537-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective formation of certain advanced glycation end products in spinal cord astrocytes of humans and mice with superoxide dismutase-1 mutation

Abstract: Recent studies have documented carbonyl stress involvement in the pathogenesis of sporadic amyotrophic lateral sclerosis (ALS). The aim of the present study was to assess a role for carbonyl stress in motor neuron degeneration associated with superoxide dismutase-1 (SOD1) mutant familial ALS and its transgenic mouse model, using an immunohistochemical investigation of advanced glycation end products (AGEs) and advanced lipoxidation end products (ALEs). In the spinal cords from six familial ALS patients with SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…3) Mutating Trp to Phe also slows the rate of aggregation of recombinant SOD-1 wt following oxidative modification in vitro (25). 4) Oxidative modification of Trp results in the formation of free carbonyl moieties that go on to form advanced glycation end products; carbonyl-containing as well as anionic detergentand dithiothreitol/␤-mercaptoethanol-resistant high molecular weight species of mutant SOD-1 have been detected in cultured cells (2,3) and in both tissues and filter-purified aggregates of transgenic mice expressing mutant SOD-1 (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Mutating Trp to Phe also slows the rate of aggregation of recombinant SOD-1 wt following oxidative modification in vitro (25). 4) Oxidative modification of Trp results in the formation of free carbonyl moieties that go on to form advanced glycation end products; carbonyl-containing as well as anionic detergentand dithiothreitol/␤-mercaptoethanol-resistant high molecular weight species of mutant SOD-1 have been detected in cultured cells (2,3) and in both tissues and filter-purified aggregates of transgenic mice expressing mutant SOD-1 (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative modification of SOD-1 has been observed in Alzheimer, Parkinson, and fALS models (7,(15)(16)(17)(18)(19)(20)40). Such oxidative modification, however, should not be regarded as inherently toxic.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs have been detected in the spinal cord and brain of ALS patients [17] and are involved in the crosslinking of neurofilament proteins. Indeed, the levels of various AGEs are higher in the Cu,Zn-SOD mutant of human and mice [18]. The relation between glycation and neurodegenerative diseases has been extensively reviewed [56].…”
Section: Protein Glycation and Oxidative Stress In Neurodegenerative mentioning
confidence: 99%
“…Various glycated proteins such as collagen [4], lens crystalline [5], albumin [6], and ribonuclease [7] are also involved in the development of diabetes and aging. β2 Microglobulin was also found to be glycated in patients with hemodialysis-associated amyloidosis [8] as well as some proteins related to neurodegenerative disorders [9] such as Alzheimer's disease (AD) [10][11][12][13], Parkinson's disease (PD) [14][15][16] and Amyotrophic lateral sclerosis (ALS) [17][18][19]. In the above neurodegenerative disorders, AGEs including Nε-(carboxylmethyl) lysine (CML) accumulate but our data also indicated that the levels of Amadori products at the early stage of glycation, were also increased.…”
Section: Glycation Of Proteinsmentioning
confidence: 99%
“…Glycation of these lysine residues impairs the self-assembly process and thereby promotes cross-linking in the neurofilament protein, which leads to ALS. Studies have revealed that AGE levels were higher in the presence of the Cu, Zn-SOD-1mutation, while in control human and mouse subjects, AGE immunoreactivities were virtually absent [67]. Strikingly, the levels of soluble RAGE (sRAGE), a C-terminal truncated isoform of RAGE, are significantly lower in the serum of ALS patients [68].…”
Section: Glycation In Amyotrophic Lateral Sclerosismentioning
confidence: 99%